Perkembangan Regulasi Digitalisasi Maritim dan Dampaknya Pada Praktik Pelayaran Modern - Wismawati Wismawati; Eliyanti Agus Mokodompit (Yayasan Cendekia Gagayunan Indonesia, 2025)
The global shipping sector is undergoing a fundamental digital transformation, adopting technologies like Maritime Autonomous Surface Ships (MASS), big data, and electronic navigation, which promise substantial gains in operational efficiency and safety. Nevertheless, the rapid pace of technological innovation has outpaced the adaptivity of conventional maritime legal frameworks, historically focused on physical safety (SOLAS, STCW) and traditional price competition (e.g., shipping conferences). This research aims to analyze the regulatory developments explicitly addressing maritime digitalization and assess their impact on modern shipping practices. Employing a normative legal research method with content analysis of international instruments (IMO, UNCLOS) and regional policies (EU), the study identifies four critical findings. First, maritime safety has mandatorily expanded to include cyber risk management through IMO Resolution MSC.428(98). Second, competition challenges have shifted from price cartels to the threat of data monopolies controlled by digital platforms. Third, MASS regulation faces serious legal ambiguity concerning liability and jurisdiction under old conventions (COLREGs, STCW). Fourth, there is a major urgency to establish a global data governance framework to overcome legal fragmentation. The implications of these findings highlight the necessity for rapid global standard harmonization and the adoption of proactive, technology-neutral regulation to ensure the shipping sector remains secure, efficient, and competitive in the digital era.